(untitled) (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
This article analyzes the integration of artificial intelligence (AI), digital simulations, and adaptive learning systems in the process of teaching Russian for specific purposes in higher military educational institutions. The study highlights the development of cadets’ professional communicative competence based on modern digital technologies, the formation of individualized learning trajectories, and the modeling of realistic military communication environments. It also provides scientific and methodological recommendations for improving Russian language acquisition through AI-based interactive dialogue systems and virtual simulations.